2018
DOI: 10.1186/s12862-018-1214-1
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine boosters the evolutionary adaptation to CoCl2 mimicked hypoxia conditions, favouring carboplatin resistance in ovarian cancer

Abstract: BackgroundOvarian cancer is the second most common gynaecologic malignancy and the most common cause of death from gynaecologic cancer, especially due to diagnosis at an advanced stage, when a cure is rare. As ovarian tumour grows, cancer cells are exposed to regions of hypoxia. Hypoxia is known to be partially responsible for tumour progression, metastasis and resistance to therapies. These suggest that hypoxia entails a selective pressure in which the adapted cells not only have a fitness increase under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 49 publications
3
27
0
Order By: Relevance
“…In the future, this approach may be applied to other chemoresistant cancers. Our previous studies suggested a stronger dependence of ES2 cells on GSH turnover compared with OVCAR3 cells [12,13], which was also evidenced in this study, as higher EC 50 of free l-BSO and l-BSO@PURE G4 -FA 2 were determined for ES2 compared with OVCAR3 cells. Furthermore, concerning resistance to carboplatin, we have reported that upon carboplatin exposure ES2 produce higher levels of GSH [11] together with an accelerated GSH turnover, compared with OVCAR3 [28].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the future, this approach may be applied to other chemoresistant cancers. Our previous studies suggested a stronger dependence of ES2 cells on GSH turnover compared with OVCAR3 cells [12,13], which was also evidenced in this study, as higher EC 50 of free l-BSO and l-BSO@PURE G4 -FA 2 were determined for ES2 compared with OVCAR3 cells. Furthermore, concerning resistance to carboplatin, we have reported that upon carboplatin exposure ES2 produce higher levels of GSH [11] together with an accelerated GSH turnover, compared with OVCAR3 [28].…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, the development of strategies to overcome chemoresistance is required for a more effective treatment of ovarian cancer [8,15,32,33]. Following our insights on ovarian cancer metabolic remodeling and therapy response [11][12][13], we posited that a FA-Rα-targeted delivery of l-BSO can be a promising strategy to revoke resistance to carboplatin (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in studies dedicated to cancer metabolism, our team showed that cysteine is beneficial for cells coping with ROS [67,68]. In monocytes, cysteine seemed to have the same role, by protecting cells against ROS effects.…”
Section: Discussionmentioning
confidence: 99%
“…Among different adaptive strategies adopted by chemoresistant cancer cells, chemoresistance has been associated with alterations in glutathione (GSH) and cysteine dynamics. We and others showed that, overall, cysteine flux in cancer cells and the expression and activity of enzymes involved in cysteine metabolism interfere with the response to chemotherapy by ultimately abrogating the effect of oxidative or alkylating drugs [ 3 , 4 , 5 , 6 , 7 ]. On the other hand, enzymes function is influenced by the oxidative stress.…”
Section: Introductionmentioning
confidence: 99%